The Role of Credit Provision in Increasing the Income of Cooperative Members of Artha Sendang Mukti Cooperative in Klepu: Analysis of Consumptive Behavior - Farihah, Fikri; Hendrajaya, Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the effect of credit provision and consumer behavior on increasing the income of cooperative members. The urgency of this study lies in the importance of optimizing the use of cooperative credit in improving the welfare of its members, especially amidst economic challenges that require wiser financial management. This study uses a quantitative approach with a survey method of 124 cooperative members selected using a purposive sampling technique. Respondents were asked to provide information related to their credit receipts and consumption habits. The data collected were analyzed using multiple linear regression to measure the effect of the two independent variables on the dependent variable, namely the increase in income of cooperative members. The results of the study indicate that credit provision has a significant effect on increasing income, with each one-unit increase in the credit provision variable contributing to an increase in income of 0.511. In contrast, consumer behavior does not have a significant effect on increasing income, indicating that the use of credit for consumption does not have a major impact on the economic welfare of cooperative members. The implications of this study emphasize that cooperatives need to focus more on providing credit for productive purposes, such as business investment and economic development of members. In addition, cooperatives are advised to provide more intensive financial education to their members so that they can manage credit more wisely and maximize its benefits in increasing income.